A position and wave spectra dataset of Marginal Ice Zone dynamics collected around Svalbard in 2022 and 2023 - Jean Rabault; Catherine Taelman; Martina Idžanović; Gaute Hope; Takehiko Nose; Yngve Kristoffersen; Atle Jensen; Øyvind Breivik; Helge Thomas Bryhni; Mario Hoppmann; Denis Demchev; Anton Korosov; et al. (Scientific Data)
Abstract Sea ice is a key element of the global Earth system, with a major impact on global climate and regional weather. Unfortunately, accurate sea ice modeling is challenging due to the diversity and complexity of underlying physics happening there, and a relative lack of ground truth observations. This is especially true for the Marginal Ice Zone (MIZ), which is the area where sea ice is affected by incoming ocean waves. Waves contribute to making the area dynamic, and due to the low survival time of the buoys deployed there, the MIZ is challenging to monitor. In 2022-2023, we released 79 OpenMetBuoys (OMBs) around Svalbard, both in the MIZ and the ocean immediately outside of it. OMBs are affordable enough to be deployed in large number, and gather information about drift (GNSS position) and waves (1-dimensional elevation spectrum). This provides data focusing on the area around Svalbard with unprecedented spatial and temporal resolution. We expect that this will allow to perform validation and calibration of ice models and remote sensing algorithms.